FAKTOR-FAKTOR YANG MEMPENGARUHI KEMISKINAN DI DAERAH ISTIMEWA YOGYAKARTA TAHUN 2003-2011 - Khurri Niswati (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2014)
This study is aimed to analyze the factors that influence poverty in Yogyakarta from 2003 to 2011. The variables used in this study are education, health, labor productivity, minimum wage of a region, and inflation. The purpose of this study are expected to analyze about how it supposed and how big are those variables influence the independent above toward poverty in Yogyakarta, which is expected to be used as a basic formulation of policy in reducing and overcoming poverty in Yogyakarta. This study uses five panel data of districts/cities during the period of 2003-2011. The data used is a secondary data obtained from the Central Statistics Bereau (CSB) and the Ministry of Manpower and Transmigration in Yogyakarta. The analysis technique used in this study is panel data with an approach of Fixed Effect Model (FEM). The results showed that (i) the poverty in Yogyakarta is high due to low education and health which is cause low labor productivity. Wages that received by workers are also under minimum wage of a region. Meanwhile, inflation has continued to increase over the last few years, (ii) education, inflation and minimum wage of region variables have no influence toward poverty in DIY. Health and labor productivity variables have negative influence to poverty in DIY and minimum wage of region has positive influence to poverty in DIY.Keywords: Poverty, Health, Labor Productivity, Minimum Wage of Region